2009
DOI: 10.1155/2009/706731
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Eigenstructure Assignment Methods and Orthogonal Eigenstructure Control of Structural Vibrations

Abstract: Abstract. This paper provides a state-of-the-art review of eigenstructure assignment methods for vibration cancellation. Eigenstructure assignment techniques have been widely used during the past three decades for vibration suppression in structures, especially in large space structures. These methods work similar to mode localization in which global vibrations are managed such that they remain localized within the structure. Such localization would help reducing vibrations more effectively than other methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…We, therefore, resort to the joint solution of ( 12) and (13). It is the intersection of the two solutions given by ( 12) and (13).…”
Section: Re-assignability: Nonzero Eigenvectors With Zero Zmentioning
confidence: 99%
See 2 more Smart Citations
“…We, therefore, resort to the joint solution of ( 12) and (13). It is the intersection of the two solutions given by ( 12) and (13).…”
Section: Re-assignability: Nonzero Eigenvectors With Zero Zmentioning
confidence: 99%
“…We, therefore, resort to the joint solution of ( 12) and (13). It is the intersection of the two solutions given by ( 12) and (13). It is systematically obtained via the null space solution of the following augmented matrix [18] (p. 8), [19] (p. 328)…”
Section: Re-assignability: Nonzero Eigenvectors With Zero Zmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic performance of structures plays an important role in engineering; however, there are always some circumstances in which structural dynamic performance does not meet the design requirements or actual situations in practice. Therefore, it is common that some existing structures need to be modified in order to acquire desired dynamic performance [1]. Many researchers have put forward many methods for the eigenstructure assignment problems [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive research results can be found in review articles [1,2] and references therein. As the dynamics of a structural system is naturally described by a set of second-order differential equations and control theory and estimation techniques are established for first-order realization of the systems, the majority of previous researches are made via transferring second-order equations to firstorder configuration (see, e.g., [3]). In the past ten years, in order not to increase the dimension of the equations and to preserve the symmetry and sparsity of the structural matrices, many authors proposed their works based directly on the second-order equation models [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%